A Qualitative Evaluation of the Phoenix Futures Recovery Through Nature Program: A Therapeutic Intervention for Substance Misuse. Issue 2 (2nd April 2016) - Aslan, Laura
ABSTRACT: The Phoenix Futures Recovery Through Nature (RtN) Program aids recovery from substance misuse through being out in a natural environment and focusing on a task, and working as a therapeutic community group to achieve it. This study set out to establish how RtN works. Findings were that the fundamental aspects of RtN—the activity, natural environment, and relationships—were key to driving changes experienced by participants; however, there were other, more subtle physical and psychological processes at play. Conclusions are that RtN is well placed to tackle addiction and should be nurtured and shared within the substance misuse community.